Optimization of RNA storage in a biobank, as well as methods for manual and automated isolation of RNA from whole blood and leukocyte fraction - S. A. Romanyuk; O. S. Popov; N. N. Sushentseva; S. V. Apalko; I. A. Polkovnikova; S. G. Shcherbak (Кардиоваскулярная терапия и профилактика)
Aim. To optimize the technique for the isolation and storage of ribonucleic acid (RNA) from whole blood and leukocyte fraction.Materials and methods. Comparison of isolation quality was carried out for RNA samples obtained from 228 leukocyte samples and 198 whole blood samples. Isolation was performed from fresh and frozen samples using ExtractRNA™ reagent and a MagNA Pure Compact automated system. Various methods of removing erythrocytes (centrifugation and treatment with hemolytic agents from two manufacturers) were tested, as well as freezing with and without preservatives for subsequent RNA isolation.Results. Twenty-one combinations of conditions were tested. The highest quality RNA was isolated by manual extraction using the ExtractRNA™ reagent from a fresh leukocyte fraction, purified by the Amplisens hemolytic agent (successful extraction — 94%, median RIN=8,4); frozen in IntactRNA™, purified by leukocyte fraction centrifugation (successful extraction — 100%, median RIN=8); frozen in ExtractRNA™, purified by leukocyte fraction centrifugation (successful extraction — 100%, median RIN=9,3).Conclusion. RNA can be isolated from frozen blood fractions, which is not inferior in quality to that isolated from fresh samples. Thus, it is not necessary to isolate RNA immediately after the receipt of biological material.